Revisiting the Role of Agriculture in Economic Growth: Can Lower Food Prices Explain the Economic Transition Status of Indonesia Relative to South Korea? - Hamzah, Ibnu Nur (Journal of Developing Economies, 2023)
The main objective of this article is to explain the possible mechanism between food prices and the economic transition status difference between Indonesia and South Korea. Moreover, the article also discusses the possible source of success in lowering food prices in the two economies. The two-goods consumption model for two economies is used to relate the relative economic transition status and food prices. The model and the historical data show a similar pattern: the economic transition is diverging between the two economies while the food prices are relatively getting more expensive in Indonesia. The possible sources of lower food prices are discussed.